A novel Anxa2-interacting protein Ebp1 inhibits cancer proliferation and invasion by suppressing Anxa2 protein level. (15th August 2015) - Zhang, Fei; Liu, Yuan; Wang, Zhiyong; Sun, Xiumei; Yuan, Jie; Wang, Tong; Tian, Ran; Ji, Wei; Yu, Man; Zhao, Yuanyuan; Niu, Ruifang
Highlights: A total of 312 proteins were identified as candidate Anxa2 interacting partners. We identified Ebp1 as a novel binding protein of Anxa2. Anxa2 and Ebp1 may function as "hubs" in the Anxa2 interaction network. Ebp1 binds to Anxa2 and regulates proliferation and invasion of breast cancer cells. Graphical Abstract: Abstract: Anxa2 is dysregulated in many types of carcinomas and implicated in several pivotal biological functions, such as angiogenesis, cell proliferation, invasion, and metastasis. We previously demonstrated that upregulation of Anxa2 enhances the proliferation and invasion of breast cancer cells. However, the detailed mechanism remains unclear. In this study, co-immunoprecipitation and LC–MS/MS-based interactome approach were employed to screen potential Anxa2 binding proteins. A total of 312 proteins were identified as candidate Anxa2 interacting partners. Using Gene Ontology, pathway annotation, and protein–protein interaction analyses, we constructed a connected network for Anxa2 interacting proteins, and Ebp1 may function as a "hub" in the Anxa2 interaction network. Moreover, Ebp1 knockdown resulted in enhanced cell proliferation and invasion, as well as increased expression of Anxa2. Furthermore, the abundance of cyclin D1 and the phosphorylation of Erk1/2 were increased in Ebp1 inhibited cells. This finding is consistent with a previous study, in which upregulation of Anxa2 results in an increased cyclin D1 expression and Erk1/2 activation. Our results suggest a novel function of Ebp1 as a binding protein and negative regulator of Anxa2. The functional association between Anxa2 and EBP1 may also participate in regulating cancer cell proliferation and invasion, thereby contributing to cancer progression.